Turkey's reconciliation efforts in the Middle East: Ambitions and constraints in a changing regional order - Salim Çevik (Stiftung Wissenschaft und Politik (SWP), 2024)
Since 2021, Turkey embarked on a Middle East reconciliation initiative involving Syria, Egypt, Israel, Saudi Arabia, and the United Arab Emirates (UAE). This initiative responds partly to evolving regional dynamics and Turkey's specific challenges, such as its protracted economic crisis and regional isolation. These reconciliation initiatives are not a single package. Although they are part of a broader process of regional reconciliation and thus interrelated, Turkey's reconciliation with each individual country has its own unique dynamics. Each case has its own drivers, strengths, and obstacles, resulting in a wide range of outcomes at the conclusion of the reconciliation initiatives. With Syria, reconciliation has remained at the level of diminished hostilities (détente), while with Egypt it has reached the level of full diplomatic normalisation of relations. Reconciliation with the UAE has gone further, and it even has the potential for a realignment between the two countries. The state of reconciliation efforts with Israel and Saudi Arabia remains uncertain and subject to constant fluctuations, especially due to the war in Gaza. Given the direct consequences of the ongoing tensions in Europe's southern neighbourhood, Europe should support Turkey's reconciliation efforts, as it will lead to a reduction in tensions in some regions, notably in Libya. However, Europe should also recognise the limits of reconciliation processes. They are compromises between regimes that are highly personalised with no institutional basis or people-to-people dimension. They are therefore inevitably unstable. In the case of Turkey, Erdoægan's constant zigzagging, his use of foreign policy for domestic political gains, and the low level of trust among his interlocutors make the reconciliation processes particularly fragile. Regional reconciliation efforts can inadvertently strengthen authoritarian regimes by making it easier to suppress dissent at home. Europe can counterbalance this by closely monitoring political refugees and critical voices, and also by offering safe haven if and when necessary.
Keywords: 320; Turkey; Middle East; Recep Tayyip Erdoægan; reconciliation initiative; regional order; Syria; Egypt; Israel; Saudi Arabia; United Arab Emirates (UAE); Hamas attack